2017
DOI: 10.1096/fj.201700292rr
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the degradation of aggregated TDP‐43 mediated by the ubiquitin proteasome system and macroautophagy

Abstract: Amyotrophic lateral sclerosis and frontotemporal lobar degeneration with ubiquitin-positive inclusions are neurodegenerative disorders that share the cytosolic deposition of TDP-43 (TAR DNA-binding protein 43) in the CNS. TDP-43 is well known as being actively degraded by both the proteasome and macroautophagy. The well-documented decrease in the efficiency of these clearance systems in aging and neurodegeneration, as well as the genetic evidence that many of the familial forms of TDP-43 proteinopathies involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…Although there is controversy regarding whether TDP-43 is overexpressed in ALS patients [13], the presence of CTFs could represent a consequence of loss in protein homeostasis that leads to protein accumulation. This is supported by the finding that TDP-43 accumulation in the cytoplasm deregulates autophagy and proteasome functions [14][15][16]. Further, the presence of CTFs could represent a cellular way to cope with the increase in protein accumulation, by cleaving it in smaller pieces that could more easily enter the ubiquitin-proteasome system (UPS) and autophagy systems [17,18].…”
Section: Tdp-43 Overexpression Induces Protein Aggregation and Fragmementioning
confidence: 89%
“…Although there is controversy regarding whether TDP-43 is overexpressed in ALS patients [13], the presence of CTFs could represent a consequence of loss in protein homeostasis that leads to protein accumulation. This is supported by the finding that TDP-43 accumulation in the cytoplasm deregulates autophagy and proteasome functions [14][15][16]. Further, the presence of CTFs could represent a cellular way to cope with the increase in protein accumulation, by cleaving it in smaller pieces that could more easily enter the ubiquitin-proteasome system (UPS) and autophagy systems [17,18].…”
Section: Tdp-43 Overexpression Induces Protein Aggregation and Fragmementioning
confidence: 89%
“…We next wanted to extend our evaluation of TFEB involvement in aggregate clearance of the protein TARDBP/TDP-43 (TAR DNA binding protein) typically characterizing sporadic forms of ALS and of fronto-lateral temporal dementia, as well as familial forms of ALS (fALS) linked to several human SOD1 (superoxide dismutase 1) mutations. In patients and cellular models of these diseases, TARDBP is cleaved releasing a neurotoxic fragment of 25 kDa (TARDBP-25/TDP-25), and we recently reported that this cleaved fragment is highly prone to aggregate into sodium dodecyl sulfate-insoluble species resistant to autophagy clearance and capable of impairing autophagy [63,64]. While no significant variations were found for the soluble fraction of the GFP-tagged TARDBP-25 fragment evaluated in WB (Figure 3(e)), similar to the AR model, we found that trehalose induced the clearance of the aggregated form of this fragment retained on FRA (Figure 3(f), quantification in Figure 3(g)).…”
Section: Tfeb Downregulation Prevents Trehalose-mediated Autophagy Inmentioning
confidence: 99%
“…In mammalian cells, the clearance of aberrantly folded or misfolded proteins is mediated by the intracellular protein quality control (PQC) system 11 . The PQC system is composed of chaperone/co-chaperone proteins, which recognize, bind to and target aberrant proteins to degradation, and the degradative systems, like the ubiquitin proteasome system and the autophagy 12 14 . Chaperones and co-chaperones work in complex; one example is represented by BAG3, a co-chaperone of HSP70 that also binds to the chaperone HSPB8, and the E3 ligase CHIP.…”
Section: Introductionmentioning
confidence: 99%